2016
DOI: 10.1096/fj.201600773r
|View full text |Cite
|
Sign up to set email alerts
|

Novel ketone diet enhances physical and cognitive performance

Abstract: Ketone bodies are the most energy-efficient fuel and yield more ATP per mole of substrate than pyruvate and increase the free energy released from ATP hydrolysis. Elevation of circulating ketones via high-fat, low-carbohydrate diets has been used for the treatment of drug-refractory epilepsy and for neurodegenerative diseases, such as Parkinson’s disease. Ketones may also be beneficial for muscle and brain in times of stress, such as endurance exercise. The challenge has been to raise circulating ketone levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 65 publications
7
109
0
1
Order By: Relevance
“…Such findings suggest that BHB is not only a biomarker of the metabolic switch and an energy source for neurons but is also a peripheral signal that activates neuronal signalling pathways that enhance synaptic plasticity, cognition and neuronal stress resistance. Indeed, it was reported that oral administration of a BHB ester to rats for 5 days improves their spatial learning and memory and enhances their endurance in a treadmill test 108 . In addition to their roles as energy substrates and signalling molecules, BHB and AcAc are also precursors to membrane lipids in brain cells, including neurons and, notably, the oligodendrocytes 109 , suggesting a benefit of IMS for axonal myelination.…”
Section: Ims-associated Peripheral Signalsmentioning
confidence: 99%
“…Such findings suggest that BHB is not only a biomarker of the metabolic switch and an energy source for neurons but is also a peripheral signal that activates neuronal signalling pathways that enhance synaptic plasticity, cognition and neuronal stress resistance. Indeed, it was reported that oral administration of a BHB ester to rats for 5 days improves their spatial learning and memory and enhances their endurance in a treadmill test 108 . In addition to their roles as energy substrates and signalling molecules, BHB and AcAc are also precursors to membrane lipids in brain cells, including neurons and, notably, the oligodendrocytes 109 , suggesting a benefit of IMS for axonal myelination.…”
Section: Ims-associated Peripheral Signalsmentioning
confidence: 99%
“…The unique ability of ketone bodies to supply energy to brain during periods of impairment of glucose metabolism make ketosis an effective treatment for a number of neurological conditions which are currently without effective therapies. Impairment of cognitive function has also been shown to be improved by the metabolism of ketone bodies . Additionally, Alzheimer's disease, the major cause of which is aging can be improved clinically by the induction of mild ketosis in a mouse model of the disease and in humans .…”
Section: Resultsmentioning
confidence: 99%
“…The inescapable fact that the brain eventually ceases to function in the complete absence of either glucose or oxygen has focussed the theories of neuroenergetics toward the oxidation of glucose as being the prime mechanism for energy acquisition of the mammalian brain. However, the ability of the brain to adapt to low glucose in insulin-injecting diabetes patients (Maran et al, 2000), to low oxygen in people at high altitude (Hochachka et al, 1996) and increased ketone body in diet (Roy et al, 2015; Murray et al, 2016) suggests that the brain makes use of more than one mechanism to acquire energy. These alternate mechanisms can compensate for decreased glucose and oxygen but can never completely replace oxygen- and glucose-dependent metabolic activities.…”
Section: Resultsmentioning
confidence: 99%